PENAPISAN SENYAWA FITOKIMIA DAN PENGUJIAN ANTIOKSIDAN EKSTRAK DAUN POHON MERAPAT (Combretocarpus rotundatus (Miq.) DARI HUTAN KERANGAS - Kissinger; Evrizal AM. Zuhud; Latifah K; Darusman; Iskandar (Jurnal Penelitian Hasil Hutan, 2013)
Kerangas forests typifies as tropical-rain vegetation trees, characterized by among others their low nutrients contents and sparse biodiversities, thereby denying their tree uses. The kerangas forests grow widespread in Kalimantan (e.g. South Kalimantan). Among the species that can grow and with stand such extreme condition is merapat (Combretocarpus rotundatus) trees. Their leaves contains particular chemical compounds that indicatively afford physiological bioactivities e.g. antioxidants. Consequentys this could expectedly emulate the added values for merapat tree uses. In relevant, scrutiny on phytochemical compounds and testing of such antioxidant efficacy were conducted on the samples of dry merapat tree-leaves taken from the kerangas forest in South Kalimantan. Initially, the dry leaves were extracted with methanol solvent, which yielded the methanol extract (i.e. sample 1), further fractionated by the column chromatography using chloroform eluant. The obtained chloroform-eluted fractions (sample 2) were fractionated again by the misced ethyl acetate-chloroform solvents (in equal proportion), which yielded the so-called sample 3. Phytochemical scrutiny revealed that the methanol extracts contained particular compounds such as flavonoids, phenol derivatives, bydroquinone, tannin, and triterpenoids, wich among them afforded the anticocidant efficacy. The methanol extract (sample 1) exchibited the very strongest antioxidant action by inflicting such reduction reaction on the free radicals released by the DPPH (2,2-diphenyl-1-picrylhydrazyl), while such action exerted by the chloroform-eluted fractions' sample 2 and the ethyl-acetate-chloroform-eluted fractions' sample 3 was very little. The inhibition of free-radical formation from DPPH as much as 50% (IC50) occurred at 21.82 ppm of the methanol-extract concentration. Meanwhile, vitamin C and BHT as the control antioxidants performed more efficiently at much less than 21.82 ppm (i.e. 6.74 and 6.28 ppm, respectively). However, such IC50 value strongly suggests that the merapat leaves' methanol extract afforded the potential bioactivity as antioxidant.